Atualização em plataforma de Ead sobre o uso de Concentrados Celulares em Odontologia - Emerick Junior, Enos [UNIFESP] (2019)
Introduction: Cellular concentrates have been used in dentistry since 1990. Their clinical use has been increased and new protocols have emerged. There is a demand for training in this technique by the dentist and e-learning can be a tool to make this knowledge available. Objective: To develop and validate content about the use of cellular concentrates in dentistry, making it available through multimedia modules in an e-learning platform. Method: The study was approved by the Research Ethics Committee of UNIFESP. A prior search was performed on PubMed, Google Scholar and Google. Bibliographic survey for content structuring was done by using “Platelet-Rich Fibrin” as keyword. Survey included studies from 2006 and with protocols for obtaining cell concentrates. Validation was done by using Delphi technique, and the implementation in e-learning platform. Results: The content has eight videos, one Study Guide and one Question Book. CVI=0.87 was obtained at validation. The content was hosted on DSP Biomedical's e-learning platform, partner in the project. Conclusion: Content of “The Use of Cellular Concentrates in Dentistry” was developed and validated, then hosted on a distance learning platform, consisting of PDF study guides and videos from each chapter of the curriculum.